Impact comminution in jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Wirth, Karl Ernst; Peukert, Wolfgang (Dynamic Flowsheet Simulation of Solids Processes, 2020)
Modelling the comminution in jet mills with respect to the complex twophase flow and the dynamic process behaviour is still a challenging task. The processed solids pass through several stages in the mill: The comminution process in the lower part, the pneumatic transport towards the classifier in the middle section, and the classification step at the top. In this contribution, the grinding kinetics and process behaviour during quasi-batch and fed-batch operational mode for different holdups, classifier speeds, and particle sizes are examined in detail. A previously developed method using well-characterized aluminium particle probes to access the stressing conditions is adapted for application in the investigated jet mill: The relative particle impact velocity is linked to the geometric changes of the particles upon impact. A high number of impact events happen in the mill, while at the same time, the average particle velocity is comparatively low. Besides the stressing conditions, breakage probabilities for the used glass beads are determined by single particle impact experiments and described by the model of Vogel and Peukert. Solids concentration measurements and high-speed imaging reveal the formation of particle clusters at the classifier and its periphery. These clusters have a massive impact on the classification step itself: Fine particles are trapped inside the clusters and are not discharged. Based on an adaption of the breakage model, and using the mean relative particle impact velocity determined by the particle probes, a model for the product mass flow is introduced.
CRIS-Team Scopus Importer:2020-08-28